B cells as a critical node in the microbiota–host immune system network. Issue 1 (July 2014) - Slack, Emma; Balmer, Maria L.; Macpherson, Andrew J.
Summary: Mutualism with our intestinal microbiota is a prerequisite for healthy existence. This requires physical separation of the majority of the microbiota from the host (by secreted antimicrobials, mucus, and the intestinal epithelium) and active immune control of the low numbers of microbes that overcome these physical and chemical barriers, even in healthy individuals. In this review, we address how B‐cell responses to members of the intestinal microbiota form a robust network with mucus, epithelial integrity, follicular helper T cells, innate immunity, and gut‐associated lymphoid tissues to maintain host–microbiota mutualism.